Enhancing Public Speaking Skills through a Collaborative Learning Approach with Performance Assessment - Nurhayatin, Titin; Fauziyyah, Desti; Hidayati, Panca; Budiarti, Any; Jamaludin, Maun (Research Horizon, 2023)
Public speaking skills offer numerous advantages in enhancing achievement and prestige. Individuals with adept public speaking abilities often garner accolades for their achievements. Moreover, within societal contexts, those proficient in public speaking are more likely to secure esteemed positions and leadership roles. Consequently, mastery of public speaking holds paramount importance in an individual's life. Aspiring teachers, especially students, must possess the capability to effectively communicate, present, and engage in public speaking activities. This study employs a quantitative approach through experimental research methods, utilizing a combined one-group pretest-posttest design. Public speaking proficiency is assessed through video-recorded practice tests, with peer evaluations focusing on content mastery, systematic presentation, performance aspects (body language, facial expressions, poise, confidence, composure, and attire appropriateness), fluency, and language usage. The pretest score averaged 2.45, while the posttest score averaged 3.65, yielding an N-Gain of 0.77. This supports the hypothesis that differences exist in students' public speaking abilities before and after employing the performance assessment-based collaboration model. The data affirms the effectiveness of the collaboration model in enhancing students' public speaking skills.